2018
DOI: 10.1177/0194599818756830
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Yield and Density in Head and Neck Malignancies

Abstract: Objective Studies have suggested that the lymph node yield and lymph node density from selective or elective neck dissections are predictive of patient outcomes and may be used for patient counseling, treatment planning, or quality measurement. Our objective was to systematically review the literature and conduct a meta-analysis of studies that investigated the prognostic significance of lymph node yield and/or lymph node density after neck dissection for patients with head and neck cancer. Data Sources The Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
(128 reference statements)
1
46
1
1
Order By: Relevance
“…We addressed this issue by including patients undergoing a combined treatment modality only if the timing of their treatments was consistent with that of chemoradiotherapy, adjuvant radiotherapy, or adjuvant chemoradiotherapy. Additionally, due to missing data, we were unable to control for surgical quality control variables such as nodal yield, which have been shown to be prognostic indicators for cancers of the head and neck . Lack of morbidity data also limited our ability to detect treatment‐associated morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We addressed this issue by including patients undergoing a combined treatment modality only if the timing of their treatments was consistent with that of chemoradiotherapy, adjuvant radiotherapy, or adjuvant chemoradiotherapy. Additionally, due to missing data, we were unable to control for surgical quality control variables such as nodal yield, which have been shown to be prognostic indicators for cancers of the head and neck . Lack of morbidity data also limited our ability to detect treatment‐associated morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, due to missing data, we were unable to control for surgical quality control variables such as nodal yield, which have been shown to be prognostic indicators for cancers of the head and neck. 60 Lack of morbidity data also limited our ability to detect treatment-associated morbidities. Finally, we did not have data on local control or disease-specific survival and could not determine how the utilized treatment modality affected disease recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent data supporting the prognostic significance of nodal yield in head and neck malignancies, this is a notable change in practice. 17,[34][35][36] In this study, we found that from 1981 to 2010, there was a significant association between African American race and decreased survival. This was previously reported by Funk et al, who found significantly lower 5-year relative survival rates in African Americans than other racial groups at all disease stages.…”
Section: Prognosis and Treatmentmentioning
confidence: 49%
“…Neck dissection nodal yields have also consistently increased for neck dissections performed on both early‐ and late‐stage patients. Given recent data supporting the prognostic significance of nodal yield in head and neck malignancies, this is a notable change in practice …”
Section: Discussionmentioning
confidence: 99%
“…We were also unable to stratify or control based on several NCCN guideline features, such as perineural invasion, lymphatic/vascular invasion, and nodal location, which were not available in the data source. Additionally, due to a lack of data, we were unable to control for nodal yields in patients who underwent neck dissection, which has been shown to be prognostic of survival in other head and neck malignancies . Although we found a survival benefit for chemoradiotherapy in late‐stage squamous cell salivary malignancy, the small size of the early‐stage patients treated with chemoradiotherapy limited the conclusions that we could draw about this group.…”
Section: Discussionmentioning
confidence: 83%